The Impact of Digital Transformation on Human Resource Development in the Online Business Paradigm - Raharjo, Itot Bian (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2024)
As digital technology continues to evolve, there is a significant shift from conventional business models towards online business models. This change encompasses various aspects, ranging from how products and services are marketed to interactions with customers. This research aims to understand the influence of digital transformation on Human Resource Development (HRD) in the context of online businesses. The research method employed in this study is a qualitative literature review, drawing data from Google Scholar from 2019 to 2023. The results indicate that in the continuously evolving digital era, digital transformation has become a necessity for every business seeking to survive and thrive, particularly in the realm of online business. HRD is a highly impacted aspect of this transformation. The paradigm shift in HRD development is not only related to technical skills but also to adaptability, continuous learning, and holistic understanding of the online business ecosystem. The urgency of this research is crucial because a deep understanding of how digital transformation affects HRD development can assist organizations and stakeholders in designing effective strategies to address challenges and capitalize on opportunities in this dynamic era of online business.